Pensions, Savings and Housing: A Life-cycle Framework with Policy Simulations - John Creedy; Norman Gemmell; Grant Scobie (New Zealand Government, The Treasury, 2014)
The objective of the paper is to explore the saving and consumption responses of a representative household to a range of policy interventions such as changes in taxes and pension settings. To achieve this, it develops a two-period life-cycle model. The representative household maximises lifetime utility through its choice of optimal levels of consumption, housing and saving. A key feature of the approach is modelling the consumption of housing services as a separate good in retirement along with the implications for saving. Importantly, the model incorporates a government budget constraint involving a pay-as-you-go universal pension. In addition, the model allows for a compulsory private retirement savings scheme. Particular attention in the simulations is given to the potential impact on household saving rates of a range of policy changes. Typically the effect on saving rates is modest. In most instances, it would take very substantial changes in existing policy settings to induce significant increases in household saving rates.
Keywords: D12; H24; H31; J26; 330; Savings; Housing; Retirement; Intertemporal elasticity of substitution; rate of interest; taxation; Sparen; Wohneigentum; Altersvorsorge; Intertemporale Entscheidung; Substitutionselastizität; Wirkungsanalyse; Simulation